National Surveillance of Occupational Exposure to the Human Immunodeficiency Virus - Maura Ricketts; Linda Deschamps; Kimberly Elmslie; Michael O’Shaughnessy (Canadian Journal of Infectious Diseases)
In September 1985, a prospective study was initiated to monitor the occurrence of occupational exposures to human immunodeficiency virus (HIV)-infected blood and body fluids in Canada. This program was coordinated by the Federal Centre for acquired immune deficiency syndrome (AIDS) (now the Division of HIV/AIDS Epidemiology at the Laboratory Centre for Disease Control). The objective was to determine the risk to workers of acquiring HIV infection as a result of exposure to HIV-infected blood and other body fluids. To be eligible, a worker must have sustained a documented parenteral, mucous membrane or skin contact exposure to blood or body fluids from an HIV-infected person. A baseline specimen was collected within a week of the exposure and then at six weeks, 12 weeks, six months and 12 months. Information concerning the type of exposure, precautions used and post exposure treatment was submitted to the Federal Centre for AIDS on standard data collection forms. All information was anonymous, identified only by a code number. Guidelines for counselling an exposed employee were provided with enrollment material. As of July 29, 1991, 414 employees have been included in the study. Two hundred and thirty-seven of the 414 exposures (57%) were needlestick injuries of which 167 (70%) were sustained by nurses. Other exposures consisted of open wound contamination, eye splashes, scalpel wounds and skin contact with blood and body fluids. To date, there have been no seroconversions among workers enrolled in the surveillance program.